Mg-sulfate can spectrally obscure siderite: implications for martian surface carbonates - Sheppard, Rachel Y.; Loizeau, Damien; Fraeman, Abigail A.; Rampe, Elizabeth B.; Pilorget, Cédric; Bibring, Jean-Pierre (Frontiers in Astronomy and Space Sciences, 2025)
IntroductionThe search for carbonates on the martian surface has been ongoing since the Viking missions. Recently the Curiosity rover observed carbonate in situ in Gale crater, however it is not visible from orbit. This study investigates the role of Mg-sulfate, one of the most common secondary minerals on Mars, in obscuring the spectral signatures of carbonates in orbital datasets.MethodsWe collect spectral images of polyhydrated Mg-sulfate and siderite physical mixtures in various proportions exposed to a dry environmental chamber. We also collect spectral images at multiple timepoints to track the temporal evolution of the mixtures as the Mg-sulfate component dehydrates from 7H2O epsomite to ~2H2O X-ray amorphous forms, particularly focusing on how sulfate dehydration impacts the visibility of carbonate absorption bands at 2.3 and 2.5 µm.ResultsOur results reveal that Mg-sulfate can obscure the carbonate signature, especially the 2.3 µm band.DiscussionThese findings suggest that Mg-sulfate deposits may mask carbonates from orbital spectrometers like CRISM and OMEGA, implying that carbonate could be present in more locations on Mars than current orbital observations indicate.